A Temporal Diversity Analysis of Brazilian Begomoviruses in Tomato Reveals a Decrease in Species Richness between 2003 and 2016 - Souza, Tadeu Araujo; Silva, João Marcos Fagundes; Nagata, Tatsuya; Martins, Thaís Pereira; Nakasu, Erich Yukio Tempel; Inoue-Nagata, Alice Kazuko (Frontiers in Plant Science, 2020)
Understanding the molecular evolution and diversity changes of begomoviruses is crucial for predicting future outbreaks of the begomovirus disease in tomato crops. Thus, a molecular diversity study using high-throughput sequencing (HTS) was carried out on samples of infected tomato leaves collected between 2003 and 2016 from Central Brazil. DNA samples were subjected to rolling circle amplification and pooled in three batches, G1 (2003–2005, N = 107), G2 (2009–2011, N = 118), and G3 (2014–2016, N = 129) prior to HTS. Nineteen genome-sized geminivirus sequences were assembled, but only 17 were confirmed by PCR. In the G1 library, five begomoviruses and one capula-like virus were detected, but the number of identified viruses decreased to three begomoviruses in the G2 and G3 libraries. The bipartite begomovirus tomato severe rugose virus (ToSRV) and the monopartite tomato mottle leaf curl virus (ToMoLCV) were found to be the most prevalent begomoviruses in this survey. Our analyses revealed a significant increase in both relative abundance and genetic diversity of ToMoLCV from G1 to G3, and ToSRV from G1 to G2; however, both abundance and diversity decreased from G2 to G3. This suggests that ToMoLCV and ToSRV outcompeted other begomoviruses from G1 to G2 and that ToSRV was being outcompeted by ToMoLCV from G2 to G3. The possible evolutionary history of begomoviruses that were likely transferred from wild native plants and weeds to tomato crops after the introduction of the polyphagous vector Bemisia tabaci MEAM1 and the wide use of cultivars carrying the Ty-1 resistance gene are discussed, as well as the strengths and limitations of the use of HTS in identification and diversity analysis of begomoviruses.